“If my husband was in the labor ward with me, my baby wouldn’t have died”; experiences on birth companionship from a tertiary health facility, Tanzania - Michael Obed Mwakyusa; Ali Said; Shekha Selemani; Musa Kakiziba; Judica Christopher; Nathanael Shauri Sirili; Fadhlun M. Alwy Al-beity (PLoS ONE, 2025)
Background Despite existing policies promoting companionship, it remains uncommon in Tanzania. Pregnant women select a trusted individual to accompany them during childbirth, providing emotional, physical, and spiritual support. The World Health Organization recommends birth companionship as integral to intrapartum care for positive maternal and fetal outcomes. Objective This study aimed to explore the experiences of pregnant women and healthcare providers regarding childbirth companionship at a tertiary health facility in Tanzania. Methods Participants were purposefully selected for qualitative exploratory interviews. Focused group discussions were conducted with pregnant women attending antenatal clinics, and in-depth interviews were held with healthcare providers at Mbeya Zonal Referral Hospital in Tanzania. Braun and Clarke’s six-step thematic analysis approach was used to analyze the data. Results Three major themes emerged: "Bonding and Learning with Spouse/Partner," "Assurance of Maternal Safety," and "Fear of Blame and Breach of Confidentiality." These themes highlight a strong desire among both pregnant women and healthcare providers for companionship during labor, particularly from male partners. Emotional support and safety were cited as key reasons. Fear, however, was identified as a major obstacle, with providers concerned about potential exposure of mistakes and pregnant women fearing a violation of their privacy rights regarding health matters. Conclusion Pregnant women expressed a strong desire for companionship throughout labor. However, companionship faced challenges due to staff shortages and inadequate privacy in labor wards. There is a pressing need to enhance childbirth companionship practices and policies in low-resource settings.